Comparison of Arbitration and Mediation in Non-Litigation Dispute Resolution: Sharia Economics in the Framework of Islamic Law and Positive Law in Indonesia - Medina Nailul Amani (Penerbit Hellow Pustaka, 2025)
Dispute resolution in Indonesia can be done through various mechanisms, two of which are arbitration and mediation, which are often used in the context of non-litigation disputes. In the context of Islamic economics, these two dispute resolution methods have particular relevance because of the principles of Islamic law that are applied in various business transactions, such as finance, banking, and commercial contracts. This study aims to compare the role of arbitration and mediation in resolving Islamic economic disputes in Indonesia, both within the framework of Islamic law and positive law. From an Islamic legal perspective, arbitration and mediation are seen as methods that are more in accordance with the principles of justice, peace, and deliberation. Meanwhile, within the framework of Indonesian positive law, both methods are regulated by laws, such as Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution and Law Number 8 of 1999 concerning Consumer Protection. Although both offer advantages in terms of efficiency and flexibility, the main difference lies in the implementation and acceptance of the resulting decisions. Arbitration produces a binding decision, while mediation prioritizes peaceful resolution that is consensual. This study is expected to provide a deeper understanding of the most effective options in resolving Islamic economic disputes in Indonesia, by considering the values ​​of Islamic law and applicable positive law.